2013
DOI: 10.1371/journal.pone.0053515
|View full text |Cite
|
Sign up to set email alerts
|

Characterization In Vitro and In Vivo of a Pandemic H1N1 Influenza Virus from a Fatal Case

Abstract: Pandemic 2009 H1N1 (pH1N1) influenza viruses caused mild symptoms in most infected patients. However, a greater rate of severe disease was observed in healthy young adults and children without co-morbid conditions. Here we tested whether influenza strains displaying differential virulence could be present among circulating pH1N1 viruses. The biological properties and the genotype of viruses isolated from a patient showing mild disease (M) or from a fatal case (F), both without known co-morbid conditions were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 69 publications
1
45
0
Order By: Relevance
“…In contrast, a recent study of 29 A(H1N1)pdm09 virus-infected southern European patients indicated no CCR5-D32 allele association with disease severity, as the CCR5-D32 allele was found in only one individual who developed mild disease (Sironi et al, 2014). We previously reported this mutation in homozygosis in a deceased patient infected with A(H1N1)pdm09 virus (Rodriguez et al, 2013). Recent controversy regarding the CCR5 contribution to severe outcome in influenza infection prompted us to design a study with strong statistical power to analyse CCR5-D32 allele association with the mortality of A(H1N1)pdm09 influenza-infected patients.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, a recent study of 29 A(H1N1)pdm09 virus-infected southern European patients indicated no CCR5-D32 allele association with disease severity, as the CCR5-D32 allele was found in only one individual who developed mild disease (Sironi et al, 2014). We previously reported this mutation in homozygosis in a deceased patient infected with A(H1N1)pdm09 virus (Rodriguez et al, 2013). Recent controversy regarding the CCR5 contribution to severe outcome in influenza infection prompted us to design a study with strong statistical power to analyse CCR5-D32 allele association with the mortality of A(H1N1)pdm09 influenza-infected patients.…”
mentioning
confidence: 58%
“…Several potential genetic determinants associated with A(H1N1)pdm09 infection have been described, including TNF (Antonopoulou et al, 2012), IFN-inducible transmembrane (Everitt et al, 2012), killer-cell immunoglobulin-like receptor (Aranda-Romo et al, 2012), complement regulatory protein CD55 (Zhou et al, 2012) and Toll-like receptor 3 (Esposito et al, 2012). Data relating to the role of chemokine receptor 5 (CCR5) in severe A(H1N1)pdm09-infected patients are contradictory and have been debated (Keynan et al, 2010;Rodriguez et al, 2013;Sironi et al, 2014).CCR5 regulates various aspects of the adaptive immune response, and a non-functional allele resulting from a 32 bp deletion (CCR5-D32), which determines a loss of expression of functional CCR5 receptor, has been detected in homo-and heterozygosity (Benkirane et al, 1997). The 3These authors contributed equally to this work.…”
mentioning
confidence: 99%
“…In a Canadian sample of 9 Caucasian patients with severe H1N1pdm09 infection Keynan et al [9] found a nearly 5-fold enrichment of CCR5Δ32 heterozygotes compared to the expectation based on allele frequency in populations with European ancestry. This association found support by the description of a fatal case of H1N1pdm09 infection: the young patient was homozygous for the CCR5Δ32 allele, a status that occurs in a small minority of subjects (0.02% to 2% depending on the population) [10]. Also, studies in a Ccr5 −/− mice have indicated that, when infected with influenza A virus, these animals display accelerated macrophage accumulation in the lungs and increased mortality compared to wild-type mice [11].…”
Section: Introductionmentioning
confidence: 72%
“…However, a CCR5-mediated uptake of other microbial antigens by DCs can also stimulate antimicrobial immune responses, resulting in an improved clearance of these pathogens [32]. These data have been supported by human and experimental studies showing that heterozygous or homozygous carriers of dysfunctional CCR5 allels infected with the influenza A virus, the West nile virus or the tick-borne encephalitis virus suffer from a more severe clinical course of the disease [33-37]. Thus, it appears that a CCR5 deficiency can have protective or detrimental effects, depending on the specific infectious agent.…”
Section: Discussionmentioning
confidence: 99%